A Case of Primary Combined Squamous Cell Carcinoma with Neuroendocrine (Atypical Carcinoid) Tumor in the Floor of the Mouth - Kenji Yamagata; Kazuhiro Terada; Fumihiko Uchida; Naomi Kanno; Shogo Hasegawa; Toru Yanagawa; Hiroki Bukawa (Hindawi Limited, 2016)
The combined squamous cell carcinoma (SCC) with neuroendocrine (atypical carcinoid (AC)) tumor is extremely rare in the head and neck. We present here the first case of SCC with AC arising in the floor of the mouth of 65-year-old man. The tumor is comprised of two components of SCC and AC in the biopsy specimen. Neuroendocrine tumor component was classified as AC from the punctate necrosis and 2-10>/10 HPF. Immunohistochemical staining was HMW-CK/34B (+) and P63 (+) in SCC and synaptophysin (+) and CD56 (+) in AC. The pathological diagnosis of SCC with AC was made from both the morphological and immunological exam. Concurrent chemoradiotherapy was performed with radiotherapy 70.2 Gy and chemotherapy of CDDP and VP-16. Although the treatment effect was complete response both of primary tumor and of neck metastases, the recurrence of the primary tumor was after 6 months. Bilateral modified radical neck dissection and tumor resection of the floor of the mouth with reconstructive surgery of anterior lateral thigh free flap were performed. Although the primary and neck tumor did not recur, the multiple lung metastases and mediastinum lymph node metastases occurred at 6 months after surgery.